Praksis lesson study for learning community dalam pembelajaran ilmu pengetahuan sosial pada sekolah menengah pertama melalui kolaborasi kolegial guru dan dosen - Aditya Nugroho Widiadi; Indah Wahyu Utami (Jurnal Teori dan Praksis Pembelajaran IPS, 2016)
The focus of this research is to describe and analyze the praxis of Lesson Study for Learning Community as an effort to enhance social studies teaching learning quality by applying lesson study activity in SMPN 2 Sumberpucung which was guided by Faculty of Social Science Universitas Negeri Malang (UM). This research used a qualitative research approach and case study research design. The main sources of this research were all the social studies teachers of SMPN 2 Sumberpucung and the lecturers of Faculty of Social Science UM which was involved in the lesson study activity on this school. Research findings has led the author to take two conclusions. First, the quality of social studies teaching learning has increased by the praxis of Lesson Study for Learning Community in SMPN 2 Sumberpucung. Second, the collegial collaboration between the teachers and the lecturers has significant contributions in the enhancement of social studies teaching learning quality. The pattern of collegial collaboration manifested in the lesson plan and reflection session, and also has observed in the open lesson session. There was dialogue and mutual learning relations within teachers and teachers, and between lecturers and teachers as well.Keywords: Social Studies, Lesson Study, Learning Community http://dx.doi.org/10.17977/um022v1i22016p077